International practice of attracting financial resources through an initial public offering of securities - Aliyev, Ulugbek (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
As international practice has shown over the past ten years, at the present stage of development, one of the promising areas of attractingforeign financial resources and, in particular, direct foreign investment is the initial public offering of securities on international financial markets